2010
DOI: 10.1111/j.1469-8749.2009.03606.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of motor problems in young children with or at risk of autism spectrum disorders, ADHD, and or developmental coordination disorder

Abstract: AIM The aim of this study was to investigate the stability of motor problems in a clinically referred sample of children with, or at risk of, autism spectrum disorders (ASDs), attention-deficit-hyperactivity disorder (ADHD), and ⁄ or developmental coordination disorder (DCD).METHOD Participants were 49 children (39 males, 10 females; mean age 5y 6mo, SD 10mo) with various developmental problems, a Movement Assessment Battery for Children (M-ABC) score on or below the 15th centile, and an IQ of 70 or more. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 18 publications
2
48
1
3
Order By: Relevance
“…Kopp et al's (2010) findings are, as previously mentioned, confounded by comorbid diagnoses and the multiple comparison problem. Van Waelvelde et al (2010) find no differences between autistic children and those judged to be 'at risk' of ADHD. Interestingly, Hilton et al (2012) found better performance in participants with ASC and ADHD than those with ASC alone.…”
mentioning
confidence: 57%
“…Kopp et al's (2010) findings are, as previously mentioned, confounded by comorbid diagnoses and the multiple comparison problem. Van Waelvelde et al (2010) find no differences between autistic children and those judged to be 'at risk' of ADHD. Interestingly, Hilton et al (2012) found better performance in participants with ASC and ADHD than those with ASC alone.…”
mentioning
confidence: 57%
“…It is important to take into account that motor abnormalities in autism are observed even in infancy and are apparent during childhood and adolescence (Brian et al, 2008; Ming et al, 2007; Provost, Lopez, and Heimerl, 2007; van Waelvede, Oostra, Dewitte, Van Den Broeck, and Jongmans, 2010). It is very likely that abnormalities of motor control development and dyspraxia can exert further negative consequences on different daily motor skills in children with ASD, and it is very probable that motor control training in early childhood could decrease severity of dyspraxia symptoms in ASD in later life (Sutera et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Deficits have been documented in gait, coordination, and in the performance of skilled movements (praxis), with a recent study demonstrating that these deficits do not improve over early childhood [4*]. The characterization of motor impairments holds great clinical significance, as motor function is critical for broader aspects of development, including language, social interaction and learning (see Table 1).…”
Section: Motor Disturbancementioning
confidence: 99%